The potential of a cross-linked human serum albumin dimer in diabetic rats as an augmenting agent for antidiabetic drugs - Taguchi, K.; Chuang, Victor; Yamasaki, K.; Kawai, K.; Maruyama, T.; Komatsu, T.; Otagiri, Masaki (2015)
Purpose: The half-life of insulin analogs and glucagon like peptide-1 (GLP-1) receptor agonist is prolonged through binding to albumin, but this may not occur in hypoalbuminemic diabetic patients with protein leaking from glomerulus and high capillary protein permeability. We previously showed that human serum albumin (HSA) dimer produced by crosslinking Cys34 of two HSA molecules with 1,6-bis(maleimido)hexane has potential as a drug carrier under high glomerular permeability conditions such as nephrosis. The aim of this study was to investigate the superior ability of a structurally defined HSA dimer as an augmenting agent for antidiabetic drugs. For this purpose, the pharmacokinetic properties of HSA dimer in diabetic rat model were evaluated. In addition, the existence of insulin analogs (insulin detemir and insulin degludec) and GLP-1 receptor agonist (liraglutide) binding sites in HSA dimer was determined. Methods: The diabetic nephropathy rat model was prepared by administering a single injection (60 mg/kg) of streptzotocin (STZ) through the tail vein of Sprague-Dawley rats. Fourteen days after STZ administration, STZ-induced diabetic nephropathy model rats were given a single injection of 111In-labeled HSA monomer or 111In-labeled HSA dimer via the tail vein. Subsequently, the 111In levels in the plasma and excised organs were determined. Site specific fluorescent probe displacement experiments were performed using warfarin potassium (WF) and dansylsarcosine (DNSS) as site I and site II specific fluorescent probes, respectively. [Results and Discussion] HSA monomer was rapidly cleared from the plasma compared to the HSA dimer in diabetic nephropathy model rats. In addition, the half-life of the HSA dimer was 1.5 times longer than the HSA monomer, which can be attributed to accumulation in the muscle. The fluorescent probe displacement experiment results for HSA monomer and dimer were similar, where insulin analogs and GLP-1 receptor agonist displaced DNSS but not WF in a concentration-dependent manner. Conclusions: The HSA dimer shows potential for use as an augmenting agent for antidiabetic drugs due to its favorable pharmacokinetic properties.